A taxonomy and framework for identifying and developing actionable statements in guidelines suggests avoiding informal recommendations - Lotfi, Tamara; Hajizadeh, Anisa; Moja, Lorenzo; Akl, Elie A; Piggott, Thomas; Kredo, Tamara; Langendam, Miranda W; Iorio, Alfonso; Klugar, Miloslav; Klugarová, Jitka; Neumann, Ignacio; Wiercioch, Wojtek; et al. (Journal of clinical epidemiology, 2022)
OBJECTIVE: To propose a taxonomy and framework that identifies and presents actionable statements in guidelines. STUDY DESIGN AND SETTING: We took an iterative approach reviewing case studies of guidelines produced by the World Health Organization and the American Society of Hematology to develop an initial conceptual framework. We then tested it using randomly selected recommendations from published guidelines addressing COVID-19 from different organizations, evaluated its results, and refined it before retesting. The urgency and availability of evidence for development of these recommendations varied. We consulted with experts in research methodology and guideline developers to improve the final framework. RESULTS: The resulting taxonomy and framework distinguishes five types of actional statements: formal recommendations; research recommendations; good practice statements; implementation considerations, tools and tips; and informal recommendations. These statements should respond to a priori established criteria and require a clear structure and recognizable presentation in a guideline. Most importantly, this framework identifies informal recommendations that differ from formal recommendations by how they consider evidence and in their development process. CONCLUSION: The identification, standardization and explicit labelling of actionable statements according to the framework may support guideline developers to create actionable statements with clear intent, avoid informal recommendations and improve their understanding and implementation by users.
Keywords: Publications; Standards; GRADE; COVID-19; Research Design; Humans; World Health Organization; Practice statements; lidé; Recommendations; Guidelines; Policy; publikace; Světová zdravotnická organizace; výzkumný projekt